APPROXIMATING ALGORITHMS: FROM DISCRIMINATING DATA TO TALKING WITH AN AI. - Hayles, N. Katherine (History & Theory, 2022)
Wendy Hui Kyong Chun's Discriminating Data: Correlation, Neighborhoods, and the New Politics of Recognition offers important tools to understand and, more importantly, transform the algorithms perpetuating and intensifying discrimination in North American societies. Unpacking her work's implications, this essay offers seven approximations—ranging from eliminating bias to rethinking the symbiotic relations between humans and computational media—as solutions to the problems she identifies. While some approximations reveal limitations in others, the clashes between them are due to the scope of the frameworks they employ. All are useful in the struggle to comprehend, in both small and large terms, the nature of the profound changes in the contemporary condition as computational media penetrate ever more deeply into the fabrics of our lives.